(untitled) (The Conference Hub, 2025)
Teaching the English language in a modern educational institution is carried out in the conditions of significant changes in the entire education system. These changes are due to the need to bring the quality of the latter in line with the requirements of modern society. But it should be noted that students have poorly formed speech development skills. Students are not always able to freely argue their speeches, draw generalized conclusions, or simply freely and arbitrarily communicate with each other. Often they try to replace lively, cultural speech with standard everyday facial expressions and gestures, i.e. primitive non-verbal ways of communication. Students find it difficult to create independent, coherent, generalized oral and written statements. Students make a large number of speech, spelling and punctuation errors. The purpose of the article is to consider the means of communication technologies from the point of view of their influence on the development of oral speech in the English language lessons.